Phonology of Kasaba with vocabulary - Chidambaranatha Pillai, V. (Publication (Annamalai University. Dept. of Linguistics), 1976)
Phonology of a Dravidian language spoken by the Kasabas, a tribal people living between the Nilgiris and the Moyar River in Tamil Nadu.